Correlation Between Colorimetric Properties and Phenolic Compounds in Aged Vinegars - Afacan, Reyhan Selin Uysal (My University, 2024)
The aged vinegars studied, which are Sherry vinegars from Jerez, Spain, with varying aging periods, are protected under the Denomination of Origin (DO). The objectives of this study were to (i) examine the impact of aging on the polyphenolic compound content and color properties of Sherry vinegars, and (ii) determine the correlation between phenolic compounds and color properties in these samples. Phenolic compounds were identified and quantified using LC-MS/MS technique, and correlation analysis was conducted between phenolic content and color properties. The results showed a statistically significant decrease in total phenolic content with increased aging. Additionally, all colorimetric properties exhibited significant changes across the samples. A notable shift from yellow to red hues was observed in the vinegars. Significant reductions in caffeic acid and gallic acid content were also found due to aging. This study is the first to analyze the correlation between phenolics and color properties in Sherry vinegars, revealing the influence of phenolic compounds on their color characteristics.
Keywords: Lc-Ms/Ms, Phenolics, Sherry Vinegar, Color Properties